Comparison of Genetic, Auditory Features, and Systemic Clinical Phenotype in 14 Families with Syndromic Hearing Loss - Zheng Z; Yan L; Ding L; Zhang Y; Wang M; Yang Y; Wu J; Chen C; Tang M; Li H (The Application of Clinical Genetics)
Zhoushu Zheng,1 Lulu Yan,2,3 Lu Ding,1 Yinghui Zhang,1 Meihong Wang,1 Yihui Yang,1 Junhua Wu,3 Changshui Chen,3 Ming Tang,1 Haibo Li2,3 1Department of Otolaryngology Head and Neck Surgery, The Affiliated Women and Children’s Hospital of Ningbo University, Ningbo, People’s Republic of China; 2The Central Laboratory of Birth Defects Prevention and Control, The Affiliated Women and Children’s Hospital of Ningbo University, Ningbo, People’s Republic of China; 3Ningbo Key Laboratory for the Prevention and Treatment of Embryogenic Diseases, The Affiliated Women and Children’s Hospital of Ningbo University, Ningbo, People’s Republic of ChinaCorrespondence: Haibo Li, The Central Laboratory of Birth Defects Prevention and Control, Women and Children’s Hospital of Ningbo University, No. 339, Liuting Road, Haishu District, Ningbo City, Zhejiang Province, People’s Republic of China, Email lihaibo-775@163.com Ming Tang, Department of Otolaryngology head and neck surgery, Ningbo Women and Children’s Hospital, No. 339, Liuting Road, Haishu District, Ningbo City, Zhejiang Province, People’s Republic of China, Email tmtm-50@163.comIntroduction: Syndromic hearing loss (SHL) is characterized by distinctive clinical phenotypes as well as genetic and phenotypic heterogeneity. More than 400 species of SHL have been described, the majority of which are autosomal dominant.Methods: 11 forms of SHL were obtained from 14 unrelated families with probands ranging in age from 5 to 78 months. The results of whole exome sequencing(WES), audiological characteristics, middle and inner ear radiological findings, and additional clinical phenotype characteristics were retrospectively analyzed.Results: Fourteen people with SHL were found. Two of them had Waardenburg syndrome, two had Branchio-Oto-Renal syndrome, two had CHARGE syndrome, and one had Treacher Collins syndrome, Kleefstra syndrome, Muenke syndrome, Osteopathia Striata with Cranial Sclerosis, Ayme-Gripp syndrome, Tatton-Brown-Rahman syndrome, Stickler syndrome, or Stapes Ankylosis with Broad Thumbs and Toes. In this investigation, ten variants were first reported.Discussion: The combination of a neonatal hearing screening and WES can diagnose syndrome-type hearing loss in infancy and childhood, according to our findings, expansion of the gene variant spectrum and phenotype for various age groups of SHL is essential and can provide valuable guidelines for clinical intervention decisions. It is imperative for medical practitioners to conduct diligent and prolonged patient monitoring due to the inherent variability in both the auditory impairment and the comprehensive clinical manifestation of SHL.Keywords: syndromic hearing loss, whole exome sequencing, neonatal hearing screening, phenotype-genotype correlations